2023
DOI: 10.1371/journal.pone.0279064
|View full text |Cite
|
Sign up to set email alerts
|

Association between vitamin D level and respiratory distress syndrome: A systematic review and meta-analysis

Abstract: Background Growing evidence suggests an association between the vitamin D levels and respiratory outcomes of preterm infants. The objective of this systematic review and meta-analysis was to explore whether premature neonates with a vitamin D deficiency have an increased risk of respiratory distress syndrome (RDS). Methods We searched PubMed, EMBASE, and the Cochrane Library up through July 20, 2021. The search terms were ‘premature infant’, ‘vitamin D’, and ‘respiratory distress syndrome’. We retrieved rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…A meta-analysis study demonstrates an association between vitamin D levels within 24 h of birth and the risk of bronchopulmonary dysplasia 41 . In a recent study vitamin-D deficiency below 30 ng/mL was associated with increased risk for respiratory distress syndrome 42 . A clinical study demonstrated that vitamin D supplementation significantly reduces serum inflammation factors and the incidence of bronchopulmonary dysplasia in preterm infants 43 .…”
Section: Resultsmentioning
confidence: 93%
“…A meta-analysis study demonstrates an association between vitamin D levels within 24 h of birth and the risk of bronchopulmonary dysplasia 41 . In a recent study vitamin-D deficiency below 30 ng/mL was associated with increased risk for respiratory distress syndrome 42 . A clinical study demonstrated that vitamin D supplementation significantly reduces serum inflammation factors and the incidence of bronchopulmonary dysplasia in preterm infants 43 .…”
Section: Resultsmentioning
confidence: 93%
“…In this study, we showed that the rate of lung surfactant utilization was higher in the low-vitamin D group than in the high-vitamin D group, and we considered that vitamin D deficiency affects lung maturation and is related to PS synthesis and secretion. The reasons are as follows [17], Vitamin D plays a key role in the development of lung function and synthesis of type II alveolar epithelial cells in fetuses and newborns. The active metabolite of vitamin D, 1,25(OH) D3, inhibits the proliferation of airway smooth muscle cells, which leads to increased responsiveness to acetylmethacholine, increased airway resistance, and altered airway structure.…”
Section: Univariate Andmentioning
confidence: 99%